One stone two birds: anti-inflammatory bronchodilators as a potential pharmacological strategy for COVID-19 - Yu, Yuanyuan; Fang, Bangjiang; Yang, Xiao-Dong; Zheng, Yuejuan (Frontiers in Pharmacology, 2023)
The ongoing Coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has imposed a huge threat to public health across the world. While vaccinations are essential for reducing virus transmission and attenuating disease severity, the nature of high mutation rate of SARS-CoV-2 renders vaccines less effective, urging quick development of effective therapies for COVID-19 disease. However, developing novel drugs remains extremely challenging due to the lengthy process and high cost. Alternatively, repurposing of existing drugs on the market represents a rapid and safe strategy for combating COVID-19 pandemic. Bronchodilators are first line drugs for inflammatory lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Compared to other anti-inflammatory drugs repurposed for COVID-19, bronchodilators are unique in that they have both anti-inflammatory and bronchodilating properties. The dual properties may empower bronchodilators greater potential to be repurposed for COVID-19, particularly pneumonia that could be better relieved by simultaneous suppression of hyperinflammation and improvement of ventilation. In fact, clinical and preclinical studies have recently emerged to investigate the efficacy of bronchodilators in treating COVID-19 pneumonia and other associated symptoms. This review will summarize recent findings in this area and highlight the promising clinical benefits and possible adverse effects of bronchodilators as therapeutic options for COVID-19.